Educação profissional em debate : da crise financeira mundial de 2008 ao arranjo institucional do PRONATEC - Reis, Cinval Filho dos (2017)
The studies hereunder presented is the elaboration of a Doctorate thesis linked to the Federal University of Uberlandia, part of its Education Faculty and Post Graduate Scheme Stricto Sensu, with line of research “State, Politics and Education Management”. The study's analysis axis is the institutional setting of the National Program of Employment Access (PRONATEC, in its Portuguese acronym) while education policy representative of the Brazilian Professional and Technological Education, guided by CEPAL organized and consolidated as response to the 2009's world financial crisis. The study's object consists of analysing the above mentioned program in its interfaces with the economic, politic and social context in world (central countries) and national (Brazilian peripheral economy) scale where the highlight was the capital accumulation regime and the world crisis roots, ignited by the crisis in the subprime mortgage market in the United States. By utilizing bibliographic research (theory fundaments of the essential categories which base the study's object) and empiric research (based on quantitative data - graphs, tables and qualitative) as methodologic procedures, a problematic was developed around the professional education provided by PRONATEC in the time frame between 2011 and 2014. In ontological, epistemological and methodological terms, this research is supported by the dialectal historic materialism, since the developed analysis were based on the search and problematization of the contradictions in the reality PRONATEC was installed - using as reference from the macro (world) to the micro (national) context. The first chapter presents a politic and economic contextualization of the PRONATEC roots, from the 2008's world financial crisis, with its respective developments in Brazil. Later, the second chapter does a critical analysis of the international organisms, in respect of CEPAL and its influences and orientations destined to PRONATEC's creation, aiming to promote employability and to install the flexisecurity model in Latin America and in Brazil. Lastly, the third chapter, developed a quantitative and qualitative critical analysis of PRONATEC's institutional setting and its social inclusive proposal via professional education, in respect to its expansion between 2011 and 2014. Thereafter, this study was structured in order to defend a thesis that the PRONATEC consists of a process of human formation influenced by the CEPAL guidelines for the aegis of the financialization of the capital. It is understood that the mortgage crisis of 2008 boosted the conservatory forming movement in the periphery of the capitalism.